Selecting a mining warehouse location - Mijalkovski, Stojance; Zeqiri, Kemajl; Mirakovski, Dejan; Mijalkovska, Daniela (Wydział Geoinżynierii, Górnictwa i Geologii Politechniki Wrocławskiej, 2024)
Choosing the optimal location for building a new or renovating an existing mining warehouse is of great importance, especially when it comes to a company that has multiple mines in different locations and needs to build one main mining warehouse. Multi-criteria decision-making finds wide application in solving many problems in mining, such as selecting the location of a main mining warehouse. When multi-criteria decision-making is applied to solve a problem, a larger number of criteria are taken into account that affect the alternatives differently, and the optimal alternative is chosen based on them. In this paper, a methodology for optimal selection of the location of the main mining warehouse will be developed using seven multi-criteria decision-making methods. After the problem has been solved using all seven methods, the resulting rankings will be compared and the optimal location of the main mining warehouse will be selected.
Mining Science, Vol. 31, 2024, s. 231-247
Keywords: górnictwo; geologia; geoinżynieria; location; warehouse; multi-criteria decision-making methods